A TRANSLATION ANALYSIS OF THE SPEECH ACT IN THE WAR SPEECH EVENT AT THE NOVEL “GHOST FLEET ; A NOVEL OF THE NEW WORLD WAR”, WRITTEN BY P.W.SINGER AND AUGUST COLE FROM ENGLISH INTO INDONESIAN - Adib Darmawan (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
Translating literary works, especially novels, causes multiple challenges for translators, including utterances consisting of some types of speech acts such directives, assertives, expressives, commissives and declaratives using proper translation techniques in accordance with their contexts. This study was especially intended to identify and analyse the types of speech acts,. It is a translation research: a case study with descriptive qualitative method on the basis of the documents of the ST and TT. The case study was applied to a novel Ghost Fleet: A Novel of  The Next World. The data were obtained using document analysis and Focus Group Discussion (FGD). The data were analyzed one by one using Spradley‟s four procedures.The results showed  that there are four types of speech acts found in the novel namely assertive, directive, expressive and comissive. The speech acts were translated using established equivalence. variation, pure borrowing, explicitation, modulation, implicitation, particularization, compensation, discursive creation, reduction, literal translation, trans-rank-shift, transposition, addition and generalization. The translation quality consisting of accuracy, acceptability and readability is very excellent.  This research revealed that in the war speech event, assertive and directive speech acts are used among the troops since the speech acts there use should contain propositions of truth to win either the combats and the war.